A comparative analysis of three pharmacovigilance system assessment tools. - Muhammad Akhtar Abbas Khan; Jude Nwokike; Asim Rauf; Zaheer-Ud-Din Babar (PLoS ONE)
Background Three key tools are currently available for assessing pharmacovigilance systems at the national level: the Indicator-Based Pharmacovigilance Assessment Tool (IPAT), the World Health Organization (WHO) Pharmacovigilance Indicators, and the Vigilance Module of the WHO Global Benchmarking Tool (GBT). These instruments are designed to evaluate the functionality and performance of national regulatory authorities within the context of their respective pharmacovigilance systems. Objectives This study aims to identify, analyze, and compare the core characteristics and operational features of these pharmacovigilance assessment tools to better understand their scope, application, and limitations. Methodology A structured document analysis was conducted on the three identified tools. The content was systematically reviewed, categorized, and synthesized to facilitate a comparative evaluation of its design, focus areas, and assessment criteria. Results The analysis revealed that the available tools encompass a broad spectrum of indicators targeting different dimensions of pharmacovigilance systems, such as infrastructure, processes, and outcomes. However, exclusive reliance on a single tool may offer a limited perspective, potentially overlooking critical components of a national pharmacovigilance framework. Conclusion This study underscores the heterogeneity of existing pharmacovigilance assessment tools and emphasizes the importance of context-specific adaptation. A tailored approach, involving the strategic selection or integration of tools, is recommended to ensure a comprehensive and accurate evaluation of national pharmacovigilance systems.